Government Strategy in Overcoming Structural Poverty in the South Coast - Anisa, Epiandri; Syafril, Rizki (Universitas Tanjungpura, 2024)
Structural poverty poses a significant challenge in many developing countries, including Indonesia. Based on the Republic of Indonesia Regulation Number 15 (2010) and the Ministry of Home Affairs Regulation Number 42 (2010), poverty alleviation requires coordinated efforts among stakeholders. This study highlights the integrated role of the community in formulating and implementing plans to reduce poverty. In the context of development, it is crucial to understand that structural poverty is often caused by the economic decline of communities, particularly related to access to land resources, such as agricultural land. The research methodology adopted is a qualitative approach with a descriptive method to depict the government's strategies in addressing structural poverty in the South coastal areas. The research findings indicate that solving structural poverty issues requires targeted adjustments to enhance long-term effectiveness and positive impact. Collaboration between the government, communities, and non-governmental organizations is key to addressing structural poverty in coastal regions. With a deep understanding of the root causes of structural poverty, it is expected that the measures taken can provide sustainable solutions and positive impacts for the affected communities.